Force-velocity characteristics and maximal anaerobic power in male recreational marathon runners - Nikolaidis, P. T.; Knechtle, B. (Research in Sports Medicine, 2020)
The aim of the present study was to examine the relationship of force-velocity (F-v) characteristics with age and race time in marathon runners. One hundred thirty-five male marathon runners (age 44.2 ± 8.8 years, height 176 ± 6 cm, body mass 24.7 ± 2.6 kg.m-2 and personal record 4:02 ± 0:45 h:min), separated into eight age groups (<30, 30-35, ., 55-60, >60 years), performed an F-v test on a cycle ergometer consisted of four 7s sprints. The older age groups had the lowest scores in maximal pedalling velocity (v0; p < 0.001, ?p2 = 0.244), relative (rPmax; p = 0.001, ?p2 = 0.176) and absolute maximal power (Pmax; p = 0.009, ?p2 = 0.135), whereas no difference in maximal force (F0; p = 0.558, ?p2 = 0.044) was shown. Race time correlated moderately with F0 (r = 0.31, p < 0.001) and Pmax (r = 0.30, p = 0.001). The small magnitude of age-related differences in anaerobic power among most age groups indicated that humans without muscle strength/power training might maintain anaerobic power indices till their sixties.